Pengaruh Job Crafting dan Work Life Integrated terhadap Kinerja melalui Kepuasan Kerja Pegawai Dinas Sosial Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Lumajang - Kiki Rohmana; Toni Herlambang; Abadi Sanosra (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of job crafting and work-life integration on employee performance through job satisfaction at the Social Service for Women's Empowerment and Child Protection of Lumajang Regency. The research method used a quantitative approach with an explanatory research design. The study population consisted of 133 employees, all of whom were sampled using a saturated sampling technique. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) assisted by WarpPLS. The results showed that job crafting had a positive and significant effect on job satisfaction (β=0.416; p<0.001) and employee performance (β=0.417; p<0.001). Work-life integration also had a positive and significant effect on job satisfaction (β=0.526; p<0.001) and employee performance (β=0.258; p=0.017). Job satisfaction has been shown to have a positive and significant effect on employee performance (β=0.505; p<0.001). Furthermore, job satisfaction mediates the effect of job crafting on employee performance (β=0.210; p<0.001) and work-life integration on employee performance (β=0.266; p<0.001). The coefficient of determination indicates that job crafting and work-life integration explain 64.5% of the variation in job satisfaction, while job crafting, work-life integration, and job satisfaction explain 85.8% of the variation in employee performance. The conclusion of this study is that job crafting and work-life integration are important factors that can improve employee performance both directly and through increased job satisfaction, with job satisfaction acting as a mediating variable that strengthens this relationship among employees of the Social Service for Women's Empowerment and Child Protection of Lumajang Regency.   Keywords: Job Crafting, Job Satisfaction, Employee Performance, Work-Life Integration